Can be marine bioactive peptides (MBAs) lead the future of foodomics for human health?. Issue 25 (1st September 2022) - Rauf, Abdur; Khalil, Anees Ahmed; Khan, Muneeb; Anwar, Sirajudheen; Alamri, Abdulwahab; Alqarni, Abdulmalik M.; Alghamdi, Adel; Alshammari, Farhan; Rengasamy, Kannan R. R.; Wan, Chunpeng
Abstract: Marine organisms are considered a cache of biologically active metabolites with pharmaceutical, functional, and nutraceutical properties. Among these, marine bioactive peptides (MBAs) present in diverse marine species (fish, sponges, cyanobacteria, fungi, ascidians, seaweeds, & mollusks) have acquired attention owing to their broad-spectrum health-promoting benefits. Nowadays, scientists are keener exploring marine bioactive peptides precisely due to their unique structural and biological properties. These MBAs have reported ameliorating potential against different diseases like hypertension, diabetes, obesity, HIV, cancer, oxidation, and inflammation. Furthermore, MBAs isolated from various marine organisms may also have a beneficial role in the cosmetic, nutraceutical, and food industries. Few marine peptides and their derivative are approved for commercial use, while many MBAs are in various pre-clinical and clinical trials. This review mainly focuses on the diversity of marine bioactive peptides in marine organisms and their production procedures, such as chemical and enzymatic hydrolysis. Moreover, MBAs' therapeutic and biological potential has also been critically discussed herein, along with their status in drug discovery, pre-clinical and clinical trials.